2019
DOI: 10.1186/s43044-019-0006-2
|View full text |Cite
|
Sign up to set email alerts
|

Transradial approach for coronary angiography and percutaneos coronary intervention: personal experience

Abstract: BackgroundThe transradial approach (TRA) has already become popular worldwide, but only recently has gained acceptance among Iraqi interventional cardiologists. The aim of this study is to document single operator experience with TRA and to test the benefit of assessing dual hand circulation before the TRA. It was an observational prospective study. Over a 2-year period (Jan 1, 2015, to Dec 31, 2016), 1561 patients underwent transradial coronary angiography (CAG) and/or percutaneous coronary intervention (PCI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
10
1
Order By: Relevance
“…Among the reasons of failure to perform PCI via radial access are failure to engage the coronary arteries, inadequate catheter support, and tortuosity of the subclavian artery or aorta. [11][12][13] Interventionalists desire to overcome this obstacle and minimize crossing over to femoral approach. Based on the findings of the present study, we believe that identifying the maximum distance of thoracic aorta curvature may help minimize the crossover rate and prevent additional radiation exposure and contrast volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the reasons of failure to perform PCI via radial access are failure to engage the coronary arteries, inadequate catheter support, and tortuosity of the subclavian artery or aorta. [11][12][13] Interventionalists desire to overcome this obstacle and minimize crossing over to femoral approach. Based on the findings of the present study, we believe that identifying the maximum distance of thoracic aorta curvature may help minimize the crossover rate and prevent additional radiation exposure and contrast volume.…”
Section: Discussionmentioning
confidence: 99%
“…There can be multiple reasons for an operator to cross over from transradial to femoral. Among the reasons of failure to perform PCI via radial access are failure to engage the coronary arteries, inadequate catheter support, and tortuosity of the subclavian artery or aorta 11‐13 . Interventionalists desire to overcome this obstacle and minimize crossing over to femoral approach.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the safety and efficacy of performing coronary angiography via the transradial access. Transradial access is preferred over transfemoral artery access for percutaneous diagnostic and interventional procedures because it is associated with lower rates of vascular and hemorrhagic complications that lead to transfusions[ 5 , 10 - 12 ]. A systematic review and meta-analysis including 11707 patients who presented with ST-segment elevation myocardial infarction, reported an association between transradial access and reduction in 30-d mortality (relative risk, 0.72), major bleeding (relative risk, 0.60), and access-site complications (relative risk, 0.40) compared with transfemoral access[ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…RAO is a potential complication of coronary angiography using the transradial approach[ 5 , 10 ]. In randomized trials, RAO incidence ranged up to 10%[ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“… 2 Nevertheless, transradial PCI is still associated with some complications, of which forearm radial artery occlusion (RAO) is the most common. Reports in the literature suggest that RAO has an incidence of 3–10% 3 or may be as high as 30%. 4 Distal transradial access (dTRA) is a new access approach for interventional therapy.…”
Section: Introductionmentioning
confidence: 99%